1984
DOI: 10.1088/0022-3727/17/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional imaging mechanisms of ocean waves by synthetic aperture radars

Abstract: Expressions are derived and discussed for the local mean intensity of the two-dimensional images of ocean waves produced by a synthetic aperture radar (SAR). Accounts are taken of the spatial and temporal changes of both back-scattered radar cross-section and ocean wave height. It is shown that the images of ocean waves are distorted as a result of radar layover. This imaging process is similar to velocity bunching by the effect is largest for range waves and it vanishes for azimuth waves. The mechanism of def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, the expression is not fundamentally dissimilar to those derived by others (e.g. Ouchi 1984). For the purpose of this paper, the approximations employed in the derivation will be described only.…”
Section: Imaging Modelmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the expression is not fundamentally dissimilar to those derived by others (e.g. Ouchi 1984). For the purpose of this paper, the approximations employed in the derivation will be described only.…”
Section: Imaging Modelmentioning
confidence: 82%
“…First, an analysis of the SAR is presented. The analysis extends the work of Ivanov (1982) and Ouchi (1984) and avoids the use o f linear superpositon with a point spread function. Secondly, it is shown that a wide range of the properties of SAR oceanic imaging follow, in a rigorous and thoroughly self-consistent way, from such an approach.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, most explicit numerical calculations have been restricted either to the linear mapping regime, for which the linear superposition 0143-1 161/90 S3.OO © 1990 Taylor & Francis Ltd principle applies, or to single sinusoidal waves (see e.g. Elachi and Brown 1977, Alpers and Rufenach 1979, Swift and Wilson 1979, Valenzuela 1980, Raney 1981, Rufenach and Alpers 1981, Rotheram 1983, Plant and Keller 1983, Ivanov 1983, Ouchi 1984, Tucker 1985, Hasselmann et al 1985. Unfortunately, the SAR imaging mechanism of ocean waves is often nonlinear, so that the SAR imaging of a continuous wave spectrum cannot be described generally by the superposition of linearly mapped sinusoids.…”
Section: Introductionmentioning
confidence: 99%